The wayfinders : why ancient wisdom matters in the modern world - Davis, Wade. (Toronto : House of Anansi Press, 2009)
"Many of us are alarmed by the accelerating rates of extinction of plants and animals. But how many of us know that human cultures are going extinct at an even more shocking rate? While biologists estimate that 18 percent of mammals and 11 percent of birds are threatened, and botanists anticipate the loss of 8 percent of flora, anthropologists predict that fully 50 percent of the 7,000 languages spoken around the world today will disappear within our lifetimes. And languages are merely the canaries in the coal mine: what of the knowledge, stories, songs, and ways of seeing encoded in these voices?" "In The Wayfinders, Wade Davis offers a gripping and enlightening account of this urgent crisis. He leads us on a fascinating tour through a handful of indigenous cultures, describing the worldviews they represent and reminding us of the encroaching danger to humankind's survival should they vanish."--BOOK JACKET.
"This book comprises the 2009 Massey Lectures, 'The Wayfinders,' broadcast in November 2009 as part of CBC Radio's Ideas series"--P. [i].
boek